Review of modern silicone and epoxy plastination methods for the brain - M. A. Kislov; K. N. Krupin; A. A. Supil'nikov; E. A. Mishurinskaya; A. N. Lysova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
In the educational process of medical and veterinary higher educational institutions, cadaveric material is actively used, which is difficult to obtain and preserve for a long time. One of the solutions for long-term preservation of educational material is the production of preparations from them using silicone and epoxy plastination methods. In this case, methods for preserving brain preparations are of value, which initially, due to its soft structure, is easily destroyed during the educational process. The article discusses new methods of brain plastination based on a sample of scientific data from PUBMED, Elibrary, Google Scholar for the period from 2017 to 2024. 14 articles from a sample of 1095 articles were analyzed. Currently, several authors propose new methods using polyester resins, additional staining for contrasting the gray and white matter of the brain, new methods of placing in acrylic boxes and creating 3D-models, processing with corn starch and enclosing in transparent thermal film, impregnation with gum arabic or paraffin, combining various plastics during plastination to improve the performance properties of the preparations.